Laparoscopic and Robotic Radical Prostatectomy Outcomes in Obese and Extremely Obese Men - Sundi, Debasish (2013)
OBJECTIVES: To evaluate operative and pathologic outcomes of laparoscopic radical prostatectomy (LRP) and robot assisted radical prostatectomy (RARP) in men with progressive changes in BMI category. METHODS: A single-surgeon series of 1,023 LRP and RARP (mostly extraperitoneal) patients was considered, of whom 987 were evaluable. Results were stratified by World Health Organization BMI category. Multivariable linear and logistic regression was used to model operating time (OT), length of stay (LOS), positive surgical margins (PSM), and noncurable cancer. RESULTS: A total of 57% (563/987) of patients were overweight and 19.6% (193/987) were obese: 152 (15.4%) BMI 30 to <35 (class I obesity), 28 (2.8%) BMI 35 to <40 (class II), and 13 (1.3%) BMI ≥ 40 (class III). There were no differences in estimated blood loss, complications, PSM, pathologic stage, or biochemical recurrence across BMI categories (6.0-month median follow-up). However, pelvic lymph node dissection was more commonly omitted and nerve-sparing score was inferior in obese men. On multivariable analysis, higher BMI was a significant predictor of longer OT. CONCLUSIONS: Obese men can safely undergo LRP or RARP, though the ability to perform excellent nerve-sparing appears to decrease with increasing obesity. Nevertheless, obese men may expect perioperative and early oncologic outcomes comparable to those of normal weight men without an increased risk of perioperative complications.